Enzyme immobilisation on electroactive nanostructured membranes (ENM): Optimised architectures for biosensing - Crespilho, Frank N. (2008)
Electroactive nanostructured membranes have been produced by the layer-by-layer (LbL) technique, and used to make electrochemical enzyme biosensors for glucose by modification with cobalt hexacyanoferrate redox mediator and immobilisation of glucose oxidase enzyme. Indium tin oxide (ITO) glass electrodes were modified with up to three bilayers of polyamidoamine (PAMAM) dendrimers containing gold nanoparticles and poly(vinylsulfonate) (PVS). The gold nanoparticles were covered with cobalt hexacyanoferrate that functioned as a redox mediator, allowing the modified electrode to be used to detect H2O2, the product of the oxidase enzymatic reaction, at 0.0 V vs. SCE. Enzyme was then immobilised by cross-linking with glutaraldehyde. Several parameters for optimisation of the glucose biosensor were investigated, including the number of deposited bilayers, the enzyme immobilisation protocol and the concentrations of immobilised enzyme and of the protein that was crosslinked with PAMAM. The latter was used to provide glucose oxidase with a friendly environment, in order to preserve its bioactivity. The optimised biosensor, with three bilayers, has high sensitivity and operational stability, with a detection limit of 6.1 [mu]M and an apparent Michaelis-Menten constant of 0.20 mM. It showed good selectivity against interferents and is suitable for glucose measurements in natural samples.